Dysgerminoma with Embryonal Carcinoma, a Rare Ovarian Malignant Mixed Germ Cell Tumor in a 13-Year-Old Girl: A Case Report - Mahsa Akbari Oryani; Farzaneh Akbari; Marjaneh Farazestanian; Sare Etemad (Mashhad University of Medical Sciences, 2024)
Introduction: Pediatric patients rarely develop ovarian tumors, but mainly develop ovarian germ cell tumors. Malignant germ cell tumors are generally rare and dysgerminoma is the most frequent malignant ovarian neoplasm in young and adolescent girls. In this study, a case of ovarian malignant mixed germ cell tumor with combination of dysgerminoma and embryonal carcinoma component is reported. Case presentation: A 13-year-old girl referred to Omid educational, research and treatment center of Mashhad with abdominal pain and swelling from five months ago and was gradually worsened. In the ultrasound examination, a mass with a cystic nature was reported in the pelvis with dimensions of 269×185mm. The patient underwent salpingo-oophorectomy surgery and tumor removal for pathological study. In the microscopic examination, 95% of malignant germ cell tumor was reported as dysgerminoma and 5% as embryonal carcinoma (CD 30 positive). The patient was discharged in good general condition to continue the treatment and receive chemotherapy. Conclusion: Any adolescent girl who develops a rapidly growing pelvic mass should be evaluated for malignant mixed germ cell tumors of the ovary, which are highly aggressive. In these patients, prompt surgical intervention with fertility preservation is crucial.